Effect of retirement on the body mass index in China: a nationwide study based on the regression discontinuity design - Jiarun Mi; Xueyan Han; Hanchao Cheng; Zhaoyang Pan; Jian Guo; Hailu Zhu; Qi Wang; Yicong Wang; Yuanli Liu; Congyi Zheng; Xin Wang; Xue Cao; et al. (BMC Public Health)
Abstract Introduction Retirement represents a significant life transition and is associated with individual health outcomes. Previous studies on the health effects of retirement have yielded inconsistent conclusions. This study aimed to estimate the impact of retirement on the body mass index (BMI) and BMI-defined overweight and obesity. Methods Between 2012 and 2015, this study included 88,471 public sector participants from the Chinese Hypertension Survey (CHS) while excluding those working in the private sector. By utilizing the fuzzy regression discontinuity design (FRDD), this research evaluated the direct impact of retirement on the BMI, as well as on the overweight and obesity rates. Additionally, the study examined variations in the effects of retirement among groups stratified by sex and educational attainment. Results The fully adjusted model suggested that retirement did not have a significant impact on the BMI or overweight and obesity rates of the overall population. Notably, retirement significantly impacted the male participants, resulting in an increase in their BMI of 2.18 (95% CI 0.23–4.13), but did not affect the BMI of the female participants. Furthermore, individuals with lower educational backgrounds experienced more pronounced BMI changes upon retirement. Conclusions On average, retirement has no significant impact on the BMI and overweight and obesity rates. Retirement leads to an increase in the BMI among men but does not affect that in women. When considering adjustments to existing retirement policies, the differential health effects of retirement across various populations should be taken into account.